Exploring the Customer’s Purchasing Decision on Thrift Clothes using Content Analysis - Dita, Ratna Karisma; Faerrosa, Lady; Pratama, Aryan Agus (Postgraduate, University of Mataram, 2024)
Thrift clothing is a product that is very popular with consumers in Indonesia. As a result, the increasing consumption of thrift clothing has attracted the attention of many academics and entrepreneurs. This research itself aims to explore consumer purchasing decisions for thrift clothing. The method used in this research is qualitative, where data collection was carried out by observing and interviewing six consumers. Data were analyzed using the content analysis method. The results of this research show that there are at least three aspects that motivate consumers to make purchases, namely product aspects (price, quality, and product availability), personal aspects (fashion taste, price expectations, and knowledge/ability to minimize risk), and social aspect (recommendation). The results of this research can be a basis for considering thrift clothing entrepreneurs to create a more customer-oriented marketing strategy; for example, if consumers are mostly students who are more sensitive to price, then the strategy can be focused on price rather than other aspects. Likewise, with the findings of other aspects, other strategies can be developed based on them.